Preparation of ZnO modified TiO2 nanoporous coatings and their photocatalytic properties. (March 2019) - Drunka, R; Grabis, J; Letlena, A; Jankovica, Dz; Krumina, A; Steins, I
Abstract: In the present work formation of active nanoporous TiO2 photocatalysts and their modification with ZnO were studied. TiO2 nanoporous coatings on Ti foil with surface area 100cm 2 were prepared by using plasma electrolytic oxidation (PEO) method in 0.5M H2 SO4 electrolyte and by using 160V DC voltage. For modification of TiO2 coatings with ZnO spray pyrolysis method where used. After preparation samples were dried and calcined at 400°C for 2h in air. Photocatalytic properties of obtained samples were tested by using degradation method of methylene blue (MB) solution under UV and VIS light illumination. Degradation rate of MB were measured by using spectrophotometer. From obtained results reaction constant (k) in the pseudo first order reaction were calculated. As prepared ZnO modified TiO2 nanoporous coating photocatalysts are with higher photocatalytic activity with respect to pure TiO2 nanoporous coating photocatalyst.